World trade, child labour, and transnational constitutionalism : the case for a new legal humanism - Humbert, Franziska (Brill/Nijhoff, 2024)
"This book argues for more coherence between human rights and trade law, analysing the world trade law compatibility of topical trade measures on (forced) child labour such as the US Tariff Act of 1930 or the proposal for an EU Forced Labour Regulation, mainly under the GATT non-discrimination principles and the policy exceptions clause"-- Provided by the publisher.
Keywords: World Trade Organization.; United States. -- Tariff Act of 1930.; World Trade Organization; Tariff Act of 1930 (United States); Child labor -- Law and legislation.; Children (International law); Foreign trade regulation.; Social responsibility of business -- Law and legislation.; Labor laws and legislation, International.; Constitutional law.; Humanism.; Enfants (Droit international); Commerce international -- Réglementation.; Humanisme.; humanism.; Child labor -- Law and legislation; Constitutional law; Foreign trade regulation; Humanism; Labor laws and legislation, International; Social responsibility of business -- Law and legislation